Gastric Perforation by Ingested Rabbit Bone Fragment - Gambaracci, Giulio (Case Rep Gastroenterol, 2016)
The majority of accidentally ingested foreign bodies is excreted from the gastrointestinal (GI) tract without any complications. Sometimes sharp foreign bodies – like chicken and fish bones – can lead to intestinal perforation and may present insidiously with a wide range of symptoms and, consequently, different diagnoses. We report the case of a 59-year-old woman presenting with fever and a 1-month history of vague abdominal pain. Computed tomography (CT) showed the presence of a hyperdense linear image close to the gastric antrum surrounded by a fluid collection and free peritoneal air. At laparotomy, a 4-cm rabbit bone fragment covered in inflamed tissue was detected next to a gastric wall perforation. Rabbit bone fragment ingestion, even if rarely reported, should not be underestimated as a possible cause of GI tract perforation.